Traditional and complementary medicine perspectives of family physicians in Istanbul - Muharrem Güner; Erdoğan Kocayiğit; Abdullah Güner; Sibel Doğan; Mahmut Tokaç; Ali Timucin Atayoglu (SERNEV, 2023)
Introduction: The World Health Organization, within the scope of the Traditional Medicine Strategy for 2014-2023, recommends the development of integrated health policies, particularly in the area of primary healthcare. However, family physicians often report feeling insufficiently trained to effectively integrate these practices into patient care. This study aims to assess the views, understanding, and experiences of family physicians regarding the utilization of Traditional amp; Complementary Medicine (T amp;CM).Methods: The family physicians employed by the Istanbul Health Directorate Public Health Services were solicited to participate in an 18-question online survey to assess their level of education in T amp;CM methods, their views on integration of T amp;CM into family medicine, and the impact of these practices on patient care.Results: A total of 324 family physicians took part in the survey; 12.0% were specialists, 64.5% had worked in primary care for over 10 years, and 59.6% were in the age range of 31-50 years. Among the physicians, the majority (70.1%) reported a preference for integrating T amp;CM practices with conventional medicine (ConvM). The majority of the participants (71.6%) had no formal T amp;CM training, and 66.4% reported inquiring about T amp;CM in their patient consultations. Over half of the physicians (56.79%) believed that T amp;CM methods should be used in preventive medicine. The most widely recognized T amp;CM technique was cupping therapy (18.5%), which was also the most frequently recommended method by physicians.Conclusion: Most of the family physicians who participated in the study expressed a desire for integrative medicine, despite acknowledging limited formal education in this field. Offering physicians training in evidence-based complementary medicine therapies could provide them with additional non-invasive treatment options. However, patients' diffidence to inform their family physicians about T amp;CM practices they undergo may pose significant risks. As a result, incorporating education on integrative medicine into formal medical education and residency training may be necessary.Keywords: Family physician, complementary medicine, integrative medicine, traditional medicine